The Effectiveness of Blog Aided Problem Based Learning Model on Learning Outcomes of Class IV Social Studies Content - Maulana, Lukmi; Ahmadi, Farid (Elementary School Teacher, 2020)
Based on the result of research in the form of observation, interviews, and data on learning outcomes conducted in the fourth grade students at Nyi Ageng Serang Cluster Elementary school in Semarang, it was known that the social studies learning outcomes were not optimal because the learning model and media used were also not optimal. Although the teacher had used problem-based learning model, the students still had difficulties to identify problems and the media in the form of A4 print out pictures were not enough to help them. This study aimed to test the effectiveness of problem-based learning model assisted by blog media on the social studies learning outcomes in fourth grade students at Nyi Ageng Serang Cluster Elementary School in Semarang. This research used quantitative approach with the experimental type and nonequivalent control group design. The sample technique used cluster random sampling, with population of 172 students. The data collection used tests, observations and documentation. The hypothesis test result showed that the value of tcount = 4.007, and ttable = 2.009, because tcount Ëƒ ttable (4.007 Ëƒ 2.009) which means that the problem based learning model assisted by blog media was effective to increase the social studies learning outcomes of the fourth grade students. The n-gain test result of the experimental group was 0.40 categorized in medium criteria, whereas the n-gain test result of control group was 0.15, categorized in low criteria. The observation of students' activities using observation sheets showed the average score of the activity of experimental class students was 82%, which is better than the control class that only got 64%. The conclusion of this research is that the problem-based learning model assisted by blog media was effectively used in social studies learning in fourth grade students at Nyi Ageng Serang Cluster Elementary School in Semarang.